RANCANG BANGUN MULTIMEDIA INTERAKTIF DENGAN MENERAPKAN MODEL PROBLEM-BASED LEARNING UNTUK MENINGKATKAN PROBLEM-SOLVING: RANCANG BANGUN MULTIMEDIA INTERAKTIF DENGAN MENERAPKAN MODEL PROBLEM-BASED LEARNING UNTUK MENINGKATKAN PROBLEM-SOLVING - Johannes Alexander Putra; Enjang Ali Nurdin; Nusuki Syariati Fathimah; Wahyudin (bit-Tech, 2024)
Informatics is intricately intertwined with the mastery of problem-solving. Within this discipline, one of the fundamental areas of study revolves around the concepts of branching and looping. During field studies, several student problems were identified, such as difficulty solving programming problems presented in the form of stories. This resulted in a lack of problem-solving skills among students when it comes to story problems. Additionally, there were issues with instructional media and less interactive teaching methods. The aim of this research is to design multimedia that implements a problem-based learning model to enhance students' problem-solving abilities. The research method used is Research and Development (R&D) with the ADDIE development model. The study involved 36 students from class X-B RPL at SMKN 1 Cimahi. The data obtained are as follows:  1) The development of interactive multimedia achieved an average score of 88. 2) There is an increase in students' problem-solving indicators, with an average pretest score of 40.13 rising to 68.38 in the posttest. Additionally, an N-Gain of 0.47 was obtained, with details as follows: understanding the problem at 0.60, devising a plan at  0.41, carrying out the plan at 0.35, and looking back at 0.34. The overall N-Gain falls within the moderate category. 3) The response to the multimedia is 83, categorized as excellent. The N-Gain results and multimedia assessment indicate that both the multimedia and this research achieved good outcomes.